Do compromisso à responsabilidade lúdica: ludismo no ensino de Química na formação básica e profissionalizante - FELÍCIO, Cínthia Maria (2011)
This work can appears like a proposal for reflections in education by chemistry in basic training, the use of playful activities as teaching resource and student engagement in the chemistry study. It can to promote a development of the play culture in the school and from school. The teacher can propose partnership and involvement of students to develop of autonomy and self-knowledge through participation in education self process. It can be a good alternative to students and teachers, when they intentionally work together to build norms and rules that should govern their actions in playgames, or games that the students participate together for a invention of theirs freedom (legaliberté) of action in the classroom through the rules of law that guarantees and serve the educational process. The teacher provides fundamental knowledge relevant to the playfulness and search experience with theirs students and build a pact of playfulness. The playfulness lived in the classroom and in activities of daily life, we believe that this can server to produce of a playgames culture, which considers the playful freedom and this legality, as a means of working the autonomy, the moral and intellectual development of students through education in chemistry. The intensification of dialogical processes and increasing intersubjectivity are seen as a stimulus to the study and understanding of the phenomena being studied. Those processes are seen as a stimulus to the study and to understand the phenomena that we are studying. Chemistry students in the basic training or professional education were challenged to participate and be involved with enthusiasm, they can do more efforts to know the concepts and answer the correctly theirs questions that the teacher or a opposite team to win the play, so they study more and do their better. So the study seem more funny pleasure study and seeks to answer the questions presented in an interdisciplinary way. Leisure activity, in which case the picnic chemical, appears as a novelty in the classroom, a way for students to share their world with peers and teachers and learn more about the chemical composition of foods preferred by them. In response to our initial question, answered by students with suggestions and ideas, seems that they know how to enjoy learning. The teacher consideration of theirs will serve as a catalyst for change and improvement in the classroom participation and sharing of information more meaningful. It could transcend the school and may be evidence for a paradigm change in the educational development of chemical concepts at college. The use of computational resource it is a strategic so good to do sense at chemistry concepts. To work with attention on language and make the students to play with perception, about the different senses of words and learn more. The educator can make questions and to encourage the students that they can participate in drawing up rules and commitment to the good performance activities of their learning process. This is essential to increase the ludic culture and environmental awareness. To learn and understand the meaning of scientific language with gain of meaning in a play activity, we have proposed interdisciplinary partnerships, information technology resources and ludism. An education based in ludic principle can help to improve education in chemistry for the development of professional autonomy and citizenship.